2019
DOI: 10.1001/jamaophthalmol.2019.2893
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pedestrian Detection With and Without Yellow-Lens Glasses During Simulated Night Driving With and Without Headlight Glare

Abstract: IMPORTANCE Some marketing materials for yellow-lens night-driving glasses claim that they increase nighttime road visibility and reduce oncoming headlight glare (HLG). However, there is no scientific evidence to support these claims. OBJECTIVE To measure the association between yellow-lens glasses and the detection of pedestrians with and without an oncoming HLG, using a driving simulator equipped with a custom HLG simulator. DESIGN, SETTING, AND PARTICIPANTS A single-center cohort study was conducted between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Of note, the US Food and Drug Administration’s Centers for Medicare & Medicaid Services 26 concluded that the manufacturer-supported, product-biased studies 24 , 25 failed to demonstrate that BLF IOLs produce clinically meaningful improved outcomes in driving safety under glare conditions. Furthermore, a recent study 27 showed that blue light–blocking spectacles do not improve pedestrian detection or reduce headlight glare in nighttime driving situations. Our study has shown that patients with BLF IOLs experienced more glare at nighttime driving, whereas other subjective disturbances were comparable between the patients with BLF and non-BLF IOLs.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the US Food and Drug Administration’s Centers for Medicare & Medicaid Services 26 concluded that the manufacturer-supported, product-biased studies 24 , 25 failed to demonstrate that BLF IOLs produce clinically meaningful improved outcomes in driving safety under glare conditions. Furthermore, a recent study 27 showed that blue light–blocking spectacles do not improve pedestrian detection or reduce headlight glare in nighttime driving situations. Our study has shown that patients with BLF IOLs experienced more glare at nighttime driving, whereas other subjective disturbances were comparable between the patients with BLF and non-BLF IOLs.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with clear lenses, none of the 3 yellow night vision glasses improved detection times with headlight glare. If anything, the yellow glasses appeared to slow older participants’ detection times for the nonglare condition (see the article’s Figure 2C).…”
mentioning
confidence: 94%
“…The behavior measured in the study was the driver’s ability to detect a pedestrian along the side of the road, or carelessly attempting to cross the road, with and without headlight glare. Unlike in Grand Theft Auto, in which colliding with the pedestrian would be considered a minor infraction, in the Hwang et al study, the driver more humanely honked the horn to signal his or her detection of the pedestrian. In some cases, the pedestrian was wearing dark clothing (blue jeans and navy blue shirt) and in other cases the pedestrian was wearing an orange Hawaiian shirt instead (undoubtedly deferring to the well-known fashion preferences of one of the authors [E.P.…”
mentioning
confidence: 97%
See 2 more Smart Citations